2019
DOI: 10.1515/nanoph-2019-0117
|View full text |Cite
|
Sign up to set email alerts
|

Designing nanophotonic structures using conditional deep convolutional generative adversarial networks

Abstract: Data-driven design approaches based on deep-learning have been introduced in nanophotonics to reduce time-consuming iterative simulations which have been a major challenge. Here, we report the first use of conditional deep convolutional generative adversarial networks to design nanophotonic antennae that are not constrained to a predefined shape. For given input reflection spectra, the network generates desirable designs in the form of images; this form allows suggestions of new structures that cannot be repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
141
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 210 publications
(154 citation statements)
references
References 25 publications
(29 reference statements)
0
141
0
Order By: Relevance
“…From the raw data of the measured image, we estimate that the unwanted zeroth-order perturbation is 19%, indicating that the total efficiency of our metasurface-based hologram is considerably high, up to 81%. We would like to underline the fact that the reported performance could be further increased, notably by properly considering near-field coupling of metasurface building blocks using optimization design methods [30][31][32][33][34][35].…”
Section: Resultsmentioning
confidence: 99%
“…From the raw data of the measured image, we estimate that the unwanted zeroth-order perturbation is 19%, indicating that the total efficiency of our metasurface-based hologram is considerably high, up to 81%. We would like to underline the fact that the reported performance could be further increased, notably by properly considering near-field coupling of metasurface building blocks using optimization design methods [30][31][32][33][34][35].…”
Section: Resultsmentioning
confidence: 99%
“…In related fields, Kim et al recently reported the use of GANs in the inverse design of porous materials [68] and So and Rho used deep convolutional GANs to generate new nanophotonic structures by inverse design. [69] Gomez-Bombarelli et al showed how a DNN and a recurrent neural network (RNN) can be used as an encoder and the decoder, respectively, for inverse design. The DNN models structure-property relationships between molecule structures and material properties and encodes the materials into latent molecule descriptors encoding molecule information.…”
Section: Inverse Designmentioning
confidence: 99%
“…Recently, machine learning (ML) has emerged as an alternative to solve complex inverse design problems of metasurfaces, [46][47][48][49][50][51] as discussed in the Malkiel et al article in this issue. 52 In ML, which is a subset of the field of artificial intelligence, the system learns a mathematical complex model by consulting past experience or example data.…”
Section: Advanced Design Algorithms For Metasurfacesmentioning
confidence: 99%
“…An alternative approach involving designing structural images instead of structural parameters has extended the degree of freedom significantly (Figure 2d). [50][51]56 Structural cross-sectional images are prepared as output forms; as a consequence, arbitrary shapes can be designed. The arbitrary shapes of such designed structures provide for the possibility that inverse design using ML could extend well beyond human intuition.…”
Section: Advanced Design Algorithms For Metasurfacesmentioning
confidence: 99%